News culture - Allan, Stuart, 1962- (Maidenhead : McGraw-Hill/Open University Press, 2011)
'News Culture' discusses the changing forms, practices and audiences of journalism. It provides an historical consideration of the rise of objective reporting in the media, and explores the presentation of the news and the cultural dynamics.
Introduction: The Culture Of News -- 1. News, Power And The Public Sphere -- 2. The Rise Of 'Objective' Newspaper Reporting -- 3. The Early Days Of Radio And Television News -- 4. Making News, Reporting Truths -- 5. The Cultural Politics Of News Discourse -- 6. News, Audiences And Everyday Life -- 7. The Gendered Realities Of Journalism -- 8. Racial Diversity In The News -- 9. War Reporting -- 10. Citizen Journalism In Times Of Crisis -- 11. 'Good Journalism Is Popular Culture.
Previous ed.: 2004.
Includes bibliographical references and index.
Keywords: Journalism -- Social aspects